2018
DOI: 10.1002/pssa.201800217
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Luminescence Properties of Ga2O3:Zn Micro‐ and Nanostructures

Abstract: High quality Zn‐doped monoclinic gallium oxide micro‐ and nanostructures are obtained by a thermal treatment based on vapor–solid (VS) growth mechanism. Nanowires and ribbons are formed, the latter being the more abundant. The microstructural features are assessed by micro‐Raman and transmission electron microscopy revealing their crystal structure properties, such as the [‐110] growth direction for ribbons and being single crystals. In particular, a strong‐scattered light polarization dependence is reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…34 Till now, there have been few studies on single-phase Ga 2 O 3 :Zn materials with high Zn content, and most of the reported components are less than 4%. 32,35…”
Section: Introductionmentioning
confidence: 99%
“…34 Till now, there have been few studies on single-phase Ga 2 O 3 :Zn materials with high Zn content, and most of the reported components are less than 4%. 32,35…”
Section: Introductionmentioning
confidence: 99%
“…[25] In the case of β-Ga 2 O 3 films deposited by pulsed laser deposition, Zn doping caused reduction of electron concentration and a relative increase in the blue luminescence at %455 nm (%2.7 eV), which is similar to the emission band at 2.7 eV observed in monoclinic Ga 2 O 3 nanostructures obtained by vapor-solid growth mechanism. [26,27] A shift of the dominant photoluminescence peak from %2.8 to %2.3 eV was also observed in Ga 2 O 3 nanostructures synthesized by thermal evaporation method. [28] β-Ga 2 O 3 thin films grown by magnetron sputtering have demonstrated a decrease in the bandgap energy with increasing Zn concentration, and improved characteristics for the metal-semiconductor-metal structure photodetectors was explained by decreased oxygen vacancy concentration.…”
Section: Introductionmentioning
confidence: 72%
“…[26] Lopez et al observed a modification of the photoluminescence in Zn-doped Ga 2 O 3 nanostructures and related the band at %2.3 eV to the presence of Zn. [27] Jiang et al reported that PL is shifted to %2.25 eV in Zn-doped Ga 2 O 3 compared with the emission centered at 2.8 eV in the undoped samples. [28] Therefore, it was important to investigate the emission in our β-Ga 2 O 3 layers.…”
Section: Resultsmentioning
confidence: 99%
“…The samples under study were fabricated following a one-step thermal treatment carried out under a controlled atmosphere and temperature. This synthesis method allows to fabricate micro- and nanostructures of diverse oxides with variable morphology and composition without the requirement of any external catalyst, template, or additional substrates, as previously reported. …”
Section: Methodsmentioning
confidence: 92%